The acute demands of repeated-sprint training on physiological, neuromuscular, perceptual and performance outcomes in team sport athletes: a systematic review and meta-analysis - Thurlow, F.; Weakley, J.; Townshend, A. D.; Timmins, R. G.; Morrison, M.; McLaren, S. J. (Sports Medicine, 2023)
Background: Repeated-sprint training (RST) involves maximal-effort, short-duration sprints (= 10 s) interspersed with brief recovery periods (= 60 s). Knowledge about the acute demands of RST and the influence of programming variables has implications for training prescription. Objectives: To investigate the physiological, neuromuscular, perceptual and performance demands of RST, while also examining the moderating effects of programming variables (sprint modality, number of repetitions per set, sprint repetition distance, inter-repetition rest modality and inter-repetition rest duration) on these outcomes. Methods: The databases Pubmed, SPORTDiscus, MEDLINE and Scopus were searched for original research articles investigating overground running RST in team sport athletes = 16 years. Eligible data were analysed using multi-level mixed effects meta-analysis, with meta-regression performed on outcomes with ~ 50 samples (10 per moderator) to examine the influence of programming factors. Effects were evaluated based on coverage of their confidence (compatibility) limits (CL) against elected thresholds of practical importance. Results: From 908 data samples nested within 176 studies eligible for meta-analysis, the pooled effects (± 90% CL) of RST were as follows: average heart rate (HRavg) of 163 ± 9 bpm, peak heart rate (HRpeak) of 182 ± 3 bpm, average oxygen consumption of 42.4 ± 10.1 mL·kg-1·min-1, end-set blood lactate concentration (B[La]) of 10.7 ± 0.6 mmol·L-1, deciMax session ratings of perceived exertion (sRPE) of 6.5 ± 0.5 au, average sprint time (Savg) of 5.57 ± 0.26 s, best sprint time (Sbest) of 5.52 ± 0.27 s and percentage sprint decrement (Sdec) of 5.0 ± 0.3%. When compared with a reference protocol of 6 × 30 m straight-line sprints with 20 s passive inter-repetition rest, shuttle-based sprints were associated with a substantial increase in repetition time (Savg: 1.42 ± 0.11 s, Sbest: 1.55 ± 0.13 s), whereas the effect on sRPE was trivial (0.6 ± 0.9 au). Performing two more repetitions per set had a trivial effect on HRpeak (0.8 ± 1.0 bpm), B[La] (0.3 ± 0.2 mmol·L-1), sRPE (0.2 ± 0.2 au), Savg (0.01 ± 0.03) and Sdec (0.4; ± 0.2%). Sprinting 10 m further per repetition was associated with a substantial increase in B[La] (2.7; ± 0.7 mmol·L-1) and Sdec (1.7 ± 0.4%), whereas the effect on sRPE was trivial (0.7 ± 0.6). Resting for 10 s longer between repetitions was associated with a substantial reduction in B[La] (-1.1 ± 0.5 mmol·L-1), Savg (-0.09 ± 0.06 s) and Sdec (-1.4 ± 0.4%), while the effects on HRpeak (-0.7 ± 1.8 bpm) and sRPE (-0.5 ± 0.5 au) were trivial. All other moderating effects were compatible with both trivial and substantial effects [i.e. equal coverage of the confidence interval (CI) across a trivial and a substantial region in only one direction], or inconclusive (i.e. the CI spanned across substantial and trivial regions in both positive and negative directions). Conclusions: The physiological, neuromuscular, perceptual and performance demands of RST are substantial, with some of these outcomes moderated by the manipulation of programming variables. To amplify physiological demands and performance decrement, longer sprint distances (> 30 m) and shorter, inter-repetition rest (= 20 s) are recommended. Alternatively, to mitigate fatigue and enhance acute sprint performance, shorter sprint distances (e.g. 15-25 m) with longer, passive inter-repetition rest (= 30 s) are recommended.